Skp2 in the ubiquitin‐proteasome system: A comprehensive review - Asmamaw, Moges Dessale; Liu, Ying; Zheng, Yi‐Chao; Shi, Xiao‐Jing; Liu, Hong‐Min (Medicinal research reviews, 2020)
The ubiquitin‐proteasome system (UPS) is a complex process that regulates protein stability and activity by the sequential actions of E1, E2 and E3 enzymes to influence diverse aspects of eukaryotic cells. However, due to the diversity of proteins in cells, substrate selection is a highly critical part of the process. As a key player in UPS, E3 ubiquitin ligases recruit substrates for ubiquitination specifically. Among them, RING E3 ubiquitin ligases which are the most abundant E3 ubiquitin ligases contribute to diverse cellular processes. The multisubunit cullin‐RING ligases (CRLs) are the largest family of RING E3 ubiquitin ligases with tremendous plasticity in substrate specificity and regulate a vast array of cellular functions. The F‐box protein Skp2 is a component of CRL1 (the prototype of CRLs) which is expressed in many tissues and participates in multiple cellular functions such as cell proliferation, metabolism, and tumorigenesis by contributing to the ubiquitination and subsequent degradation of several specific tumor suppressors. Most importantly, Skp2 plays a pivotal role in a plethora of cancer‐associated signaling pathways. It enhances cell growth, accelerates cell cycle progression, promotes migration and invasion, and inhibits cell apoptosis among others. Hence, targeting Skp2 may represent a novel and attractive strategy for the treatment of different human cancers overexpressing this oncogene. In this review article, we summarized the known roles of Skp2 both in health and disease states in relation to the UPS.